2019
DOI: 10.1016/j.conbuildmat.2019.04.191
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of a unidirectional pultruded composite lamina using micromechanics and numerical homogenization

Abstract: h i g h l i g h t s A continuum damage model was implemented via user material subroutine to model fiber failure. The Mohr-Coulomb plastic criterion were used to model the epoxy behavior. The cohesive surfaces were used to simulate the fiber-matrix interface damage. Different analytical micromechanics theories were verified by the test results. Numerical homogenization methods effectively predicted the pultruded lamina macroscopic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The obtained results were verified by the traction/compression and shear test. The experiments indicated that both obtained theoretical and numerical prediction values are in agreement with the results of experimental verifications confirming the validity of the methodology in providing a reliable reference for the structural design of pultruded fiber-reinforced polymer composite structures (FRP) [ 43 ].…”
Section: Introductionmentioning
confidence: 54%
“…The obtained results were verified by the traction/compression and shear test. The experiments indicated that both obtained theoretical and numerical prediction values are in agreement with the results of experimental verifications confirming the validity of the methodology in providing a reliable reference for the structural design of pultruded fiber-reinforced polymer composite structures (FRP) [ 43 ].…”
Section: Introductionmentioning
confidence: 54%
“…The combination of mesoscale computational homogenization triggered by the physically based model and uncoupled phenomenological model is promising to predict the ductile fracture of HSS from only the uniaxial stress–strain relationship 32–34 . The mesoscale computational homogenization method could be used to identify the fracture strain at different stress status for the calibration of the parameters of the uncoupled phenomenological model.…”
Section: Introductionmentioning
confidence: 99%
“…Although material testing is usually the most reliable approach to obtain credible data for design, it is costly, time-consuming, and thus impractical and very limited in its applicability for structural design purposes. For these reasons, the micromechanics approach, the technique used to obtain values of composite materials, is often adopted, whereby relatively accurate homogenization models are used to predict the equivalent properties of laminated composites [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of ply properties by micromechanics is well-defined, and the engineering constants of each layer can be computed from existing micromechanics models, such as rule of mixtures (LM), improved rule of mixtures (IL), and periodic microstructure (PM), whereby each layer is modeled as a homogeneous, linearly elastic, and generally orthotropic material [ 21 , 22 , 23 ]. Based on ply properties and lay-up, the apparent stiffnesses of the face laminate can be predicted by classical lamination theory (CLT) [ 24 , 25 ], and the micromechanical solution is also used for the evaluation of equivalent strength parameters of the laminates of FRP structures [ 18 , 26 ]. For the determination of strength parameters, micromechanics based on both analytical (linear model, improved fiber buckling method, fracture mechanics, strain amplification method, etc.)…”
Section: Introductionmentioning
confidence: 99%